Experimental Research on the Adhesion Characteristics of Clay to Structures with Different Materials - Tao Qiu; Yonggang Zhang (Geofluids)
When the shield machine passes through the clay layer, the clay debris cut by the cutter head usually adheres to the surface of the cutter head and is easy to form mud cakes after extrusion, which affects the safety and efficiency of construction. For the structure made of different materials, due to the different surface properties, the adhesion characteristics of clay are also different. So, selecting proper materials for the soil contacting parts in the shield machine can effectively reduce the adhesion between the structure and soil, decrease the clay adhering to the surface of the shield cutter, and reduce the possibility of further productions of mud cake. Therefore, studying the adhesion properties of clay to different materials and understanding the adhesion rule of clay to soil contacting structures are of guiding significance when selecting the materials of soil contacting parts. In this paper, the adhesion properties of cohesive soil to commonly used construction materials were studied by a self-made adhesion test device, including steel, iron, copper, aluminum, and engineering plastics (polyamide). According to the findings, the separation process of adhesion between soil and the structure by an external force can be divided into four stages, which are the adhesive elastic development stage, adhesive plastic development stage, failure stage, and detachment stage. The adhesion forces and the amount of soil adhered to the structures made of the selected materials are found to vary from each other. The adhesion forces ranked from high to low are, respectively, found on the iron, plastic, aluminum, steel, and copper surfaces. The material with the most amount of adherent soil is aluminum, followed by iron, steel, copper, and plastic.